Pengaruh Nilai Pelanggan dan Kualitas Layanan Terhadap Kepuasan dan Dampaknya Terhadap Loyalitas Pelanggan Maxx Cofee Benton Junction Lippo Karawaci, Tangerang, Banten - innocentius bernarto (PolimdoSains, 2020)
The growing retail business of coffee shops in Indonesia makes retail companies need to be able face big competitive competition in the market in order to maintain their existence. The purpose of this study is to find out whether customer value and service quality could have positive influence to customer satisfaction, and to know whether customer satisfaction have positive influence to customer loyalty of Maxx Coffee Benton Junction Lippo Karawaci. Data collection was done by using questionnaire instrument. The population in this study were the customer of Maxx Coffee Benton Junction Lippo Karawaci. The number of samples in this study were 100 respondents with convenience sampling technique. In performing statistical analysis, PLS-SEM (Partial Least Squares-Structural Equation Modeling) was used with using SmartPLS 3.2.7 as the software. The results showed that customer value and service quality have positive influence to customer satisfaction and customer satisfaction have positive influence to customer loyalty of Maxx Coffee Benton Junction Lippo Karawaci.